IDENTIFIKASI KENDALA DAN MASALAH DALAM PROSES PEMBELAJARAN MATEMATIKA - Zulkahfi Dalimunthe (Jurnal Sosial Humaniora Sigli, 2020)
The purpose of this study is to identify the constraints and problems faced by teachers in junior high school mathematics learning. The subjects in this study were mathematics teachers from ten junior high school level in Pidie Jaya district, amounting to 15 people with purposive sampling. This type of research is descriptive qualitative. The research data was obtained from the results of MGMP activities (Subject Teacher Consultation) with two categories, namely material that was difficult to teach, and a difficult learning process for certain material. The results of the study show that some material that is difficult to teach is the sequence and series, congruence, statistics, algebra (rank in roots), geometry, opportunities, and equations and linear inequalities. For the learning process that is felt difficult for certain materials, namely Algebra (KPK, FPB and SPLDV), Series / pattern numbers, congruence, not actual rank, comparison, flat build, and statistics. Keywords: constraints, problems, learning mathematics, difficult material